The intellectual property regime and the protection of the resources and traditional knowledge in Malaysia / Zara Aina Mohd Zawawi, Roza Felina Zamzuri and Sharifah Zulia Balqish S. Agil. - Mohd Zawawi, Zara Aina; Zamzuri, Roza Felina; S. Agil, Sharifah Zulia Balqish (2007)
This research project was carried out by a group of three persons, namely: Zara Aina binti Mohd Zawawi, Roza Felina binti Zamzuri and Sharifah Zulia Balqish S. Agil. Zara Aina and Roza Felina's contribution to the project paper has been among others, to gather information, to borrow books from the library, and to search for the relevant law and materials on this topic. Sharifah Zulia Balqish's contribution to the project paper has been among others, to prepare the outline of this project paper. All other works and preparation process for this project paper has been done equally by authors.